Comparison of platinum photodeposition processes on two types of titanium dioxide photocatalysts. Issue 16 (9th April 2020) - Yamamoto, Muneaki; Minoura, Yasuhiro; Akatsuka, Masato; Ogawa, Satoshi; Yagi, Shinya; Yamamoto, Akira; Yoshida, Hisao; Yoshida, Tomoko
Abstract : The photodeposition method is useful for the preparation of metal-loaded photocatalysts, by which the metal precursors are adsorbed on the photocatalyst surface and reduced by photoexcited electrons to typically form metallic nanoparticles. Abstract : The photodeposition method is useful for the preparation of metal-loaded photocatalysts, by which the metal precursors are adsorbed on the photocatalyst surface and reduced by photoexcited electrons to typically form metallic nanoparticles. In the present study, the photodeposition process of Pt nanoparticles was investigated on anatase and rutile TiO2 photocatalysts. It was found that on the anatase surface, only some of the Pt 4+ precursors were first adsorbed in an adsorption equilibrium and reduced to form a smaller number of initial metal species; then, they functioned as electron receivers to reduce the remaining precursors on their metallic surfaces and become larger particles. In contrast, the rutile surface can adsorb most of the precursors and quickly reduce them upon photoirradiation to form nanoparticles, giving a larger number of small nanoparticles. As a result, the Pt-loaded rutile photocatalyst exhibited higher activity in hydrogen evolution from an aqueous methanol solution than the Pt-loaded anatase photocatalyst.